Development of E-Learning Method as a Digital-Based Legal Information Medium in the Development of National Law - I Made Aditya Mantara Putra; Gede Agung Wirawan Nusantara; Hartini Sarifan (Journal Equity of Law and Governance, 2023)
The paradigm shift in Legal Education in Indonesia is currently being felt by academics, practitioners, students and the public, namely the technology-based learning pattern. As previously known, the pattern of learning in Indonesia is still done conventionally and conventionally on reading literacy. However, under current conditions, academics, practitioners and the public in Indonesia are expected to be able to adapt to current technological developments. The aims research to know how is the application of technology and information in providing information and legal education to the younger generation and society and to know how will the e-learning development model as a digital-based forum and source of legal information contribute to increasing public knowledge and legal awareness in the future development of national law. The research method used in this study is the normative legal method. obtained are by developing digital-based e-learning which is expected to be able to help the younger generation and the Indonesian people to understand and be aware of existing laws. In addition, the development of e-learning methods can be used as a forum for the presentation of digital-based legal information and provide a space for the community to search, research, analyze and share information effectively and efficiently. The public will quickly receive ideas and information about the law and the educational process that needs to be developed, and quality human resources in print who understand the existing laws and are able to use the technology necessary to compete in the current and future era of globalization.